Surplus charge injection enables high-cell-potential stable 2D polyaniline supercapacitors. (20th March 2023) - Jiang, Xinglin; Chu, Xiang; Zhang, Xiong; Xie, Yanting; Yang, Tao; Huang, Junfeng; Li, Wen; Deng, Weili; Zhang, Haitao; Yang, Weiqing
Abstract: The extraordinary pseudocapacitance of polyaniline (PANI) can be only realized in acid electrolytes with a limited potential window of 0.6∼0.8 V. As the potential further increases, PANI will suffer from the hydrolysis issue, leading to molecular-chain fracture and oxidative failure. In this work, we propose a strategy of surplus electron injection to stabilize the molecular chain of PANI at high cell potential. The surplus electron injection in 2D PANI is realized by exceeding the stable potential induced by an asymmetric supercapacitor structure design. As excessive charges are poured, supramolecular hydrogen bonds presented at 2D PANI capture them and generate additional redox reaction, which suppresses the damage of 2D PANI molecular structure and simultaneously strengthens its capacitive behavior. This effect is vividly demonstrated by the modulated electronic structure as indicated by shifting up the Fermi level, shifting down the work function and increasing the electrical conductivity. Consequently, high cell potential (1.2 V) 2D PANI supercapacitors with sulfuric acid electrolyte deliver a much longer cycling lifetime (76.8% vs. 45.1% after 10, 000 cycles) and a much higher energy density (19.9 vs. 7.53 Wh kg ‒1 ) than that of low cell potential (0.8 V) 2D PANI counterpart. This work guides to a novel way to design high cell potential aqueous-solution supercapacitors.